The Childbirth Experience Questionnaire (CEQ)-Validation of its use in a Danish-speaking population of new mothers stimulated with oxytocin during labour. - Sidsel Boie; Henrik Hein Lauridsen; Julie Glavind; Mette Kiel Smed; Niels Uldbjerg; Pinar Bor (PLoS ONE, 2020)
BACKGROUND:When determining optimal treatment regimens, patient reported outcomes including satisfaction are increasingly appreciated. It is well established that the birth experience may affect the postnatal attachment to the newborn and the management of subsequent pregnancies and deliveries. As we have no robust validated Danish tool to evaluate the childbirth experience exists, we aimed to perform a transcultural adaptation of the Childbirth Experience Questionnaire (CEQ) to a Danish context. METHODS:In accordance with the COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN), we translated the Swedish-CEQ to Danish. The Danish-CEQ was tested for content validity among 10 new mothers. In a population of women who have had their labour induced, we then assessed the electronic questionnaire for validity and reliability using factor analytical design, hypothesis testing, and internal consistency. Based on these data, we determined criterion and construct responsiveness in addition to floor and ceiling effects. RESULTS:The content validation resulted in minor adjustments in two items. This improved the comprehensibility. The electronic questionnaire was completed by 377 of 495 women (76.2%). The original Swedish-CEQ was four-dimensional, however an exploratory factor analysis revealed a three-dimensional structure in our Danish population (Own capacity, Participation, and Professional support). Parous women, women who delivered vaginally, and women with a labour duration <12 hours had a higher score in each domain. The internal consistency (Cronbach's alpha) ranged between 0.75 and 0.89 and the ICC between 0.68-0.93. We found ceiling effects of 57.6% in the domain Professional support and of 25.5% in the domain Participation. CONCLUSION:This study offers transcultural adaptation of the Swedish-CEQ to a Danish context. The 3-dimensional Danish-CEQ demonstrates construct validity and reliability. Our results revealed significant ceiling effect especially in the domain Professional support, which needs to be acknowledged when considering implementing the Danish-CEQ into trials and clinical practice.